Religion and American politics : from the colonial period to the 1980s - Noll, Mark A., 1946- (Oxford University Press, 1990)
In this collection of previously unpublished essays, seventeen leading scholars examine the relation between politics and religion in America before and after the Civil War. The essays examine how religious beliefs and practices have shaped political thought and behaviour (and vice versa), and how in certain periods religious and political thought has coincided or moved in opposition, and how minority perspectives have challenged majority views. Amongst the distinguished contributors are: John Murrin, Harry Stout, John F. Wilson, Daniel Walker Howe, Bertram Wyatt-Brown, Robert Swierenga, Martin Marty, Robert Wuthnow, and George Marsden.